Improving C=N Bond Reductions with (Cyclopentadienone)iron Complexes: Scope and Limitations. Issue 4 (12th October 2018) - Cettolin, Mattia; Bai, Xishan; Lübken, Dennis; Gatti, Marco; Facchini, Sofia Vailati; Piarulli, Umberto; Pignataro, Luca; Gennari, Cesare
Abstract : Herein, we broaden the application scope of (cyclopentadienone)iron complexes 1 in C=N bond reduction. The catalytic scope of pre‐catalyst 1b, which is more active than the "Knölker complex" (1a ) and other members of its family, has been expanded to the catalytic transfer hydrogenation (CTH) of a wider range of aldimines and ketimines, either pre‐isolated or generated in situ. The kinetics of 1b ‐promoted CTH of ketimine S1 were assessed, showing a pseudo‐first order profile, with TOF = 6.07 h –1 at 50 % conversion. Moreover, the chiral complex 1c and its analog 1d were employed in the enantioselective reduction of ketimines and reductive amination of ketones, giving fair to good yields and moderate enantioselectivity. Abstract : The catalytic transfer hydrogenation of imines and the reductive amination of carbonyl compounds have been thoroughly investigated with a cyclooctene‐derived (cyclopentadienone)iron pre‐catalyst. Additionally, enantioselective ketimine reduction with a chiral (cyclopentadienone)iron complex is reported here for the first time.